The History of Legal Theory and the Study of Biblical Law. - BERMAN, JOSHUA (Catholic Biblical Quarterly, 2014)
An essay is presented on the historical evolution of the law through the nineteenth century, and the judicious study of biblical law. It discusses the two views of law in jurisprudence in the 19th century which are the law as emanating from a sovereign, and the law as a complete and finite system. It also discusses whether the legal and nonlegal genres of the codes of law are of false dichotomy.